2006
DOI: 10.1111/j.1460-2466.2007.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Priming Crime and Activating Blackness: Understanding the Psychological Impact of the Overrepresentation of Blacks as Lawbreakers on Television News

Abstract: Two experiments examined the extent to which U.S. viewers' perceptions that Blacks face structural limitations to success, support for the death penalty, and culpability judgments could be influenced by exposure to racialized crime news. Participants were exposed to a majority of Black suspects, a majority of White suspects, unidentified suspects, and noncrime news stories. In addition, participants' prior news viewing was assessed. In Study 1, heavy news viewers exposed to unidentified perpetrators were less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 52 publications
(157 reference statements)
5
92
3
Order By: Relevance
“…This effect is in the range found by prior surveys (Dixon, 2008b) and experiments (Dixon & Azocar, 2007). This small effect size may be mainly due to the design of the present study.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…This effect is in the range found by prior surveys (Dixon, 2008b) and experiments (Dixon & Azocar, 2007). This small effect size may be mainly due to the design of the present study.…”
Section: Discussionsupporting
confidence: 43%
“…Experiments have shown that negative depictions of minorities can activate stereotypic attitudes in the audience (Dixon & Azocar, 2007;Domke, 2001;Gilliam & Iyengar, 2000;Power, Murphy, & Coover, 1996). Survey studies also indicate that news exposure is related to biased perceptions (Armstrong, Neuendorf, & Brentar, 1992) and attitudes toward ethnic minorities (Dixon, 2008a(Dixon, , 2008bVergeer, Lubbers, & Scheepers, 2000).…”
mentioning
confidence: 99%
“…Notably, even the presentation of single exemplars is likely to activate negative stereotypes that can color the perceptions of a whole social group (Bodenhausen, Schwarz, Bless, & Wänke, 1995;Dixon & Azocar, 2007). Other experiments also reveal that racial cues produce negative perceptions of minorities, such as dispositional attributions (Power, Murphy, & Coover., 1996), social judgments (Ford, 1997), or policy opinions (David, 2009;Domke, 2001).…”
mentioning
confidence: 99%
“…Constant exposure to media stereotypes makes them chronically accessible, especially for heavy media consumers. Even subtle, implicit cues such as varying the racial composition (African-American or White American) of criminal suspects in the news (Dixon & Azocar, 2007), facial features and skin tone of alleged offenders (Oliver, Jackson, Moses, & Dangerfield, 2004), and racial/ethnic identity of subjects in the photograph of online news stories (Abraham & Appiah, 2006) are sufficient to influence subsequent social reality judgments.…”
Section: B Media Priming and Stereotype Activationmentioning
confidence: 99%
“…Typically, the conditions include majority group members only, minority group members only, or a mix of both. For instance, Dixon and Azocar (2007) varied the racial composition of suspects in news stories to be majority Black or majority White. Very rarely, studies include media portrayals of more than one minority group, which allows for studying comparative stereotyping effects among minority groups (Ramasubramanian & Oliver, 2007).…”
Section: Independent Variablesmentioning
confidence: 99%